Review of the Ambrysus stali La Rivers species complex (Heteroptera: Nepomorpha: Naucoridae) with the description of a new species from Mesoamerica - Sites, Robert W.; Reynoso-Velasco, Daniel (Zootaxa, 2015)
The Neotropical Ambrysus stali La Rivers species complex is reviewed and includes A. bifidus La Rivers & Nieser, A. scolius La Rivers, A. stali La Rivers, and A. tricuspis La Rivers. Ambrysus oblongulus Montandon is removed as a member of this complex. Features uniting these species are related to male genitalia and associated structures. Ambrysus maya n. sp. is the fifth species in the complex and is described from Belize, Guatemala, and Mexico based on specimens from recent collecting and museum collections.